Clinical and bacteriological profile and antibiotic sensitivity pattern in spontaneous bacterial peritonitis among children with idiopathic nephrotic syndrome - Akbar, Romana; Roy, Ranjit Ranjan; Sharmim, Shanjida; Ali, M. Asif (International Journal of Contemporary Pediatrics, 2024)
Background: Spontaneous bacterial peritonitis is a serious complication of childhood nephrotic syndrome (NS). A precise knowledge of organism causing peritonitis is important primarily to treat infection and decrease morbidity, prevent antibiotic resistance and finally to reduce mortality. Objectives were to observe the clinical and bacteriological profile and antibiotic sensitivity pattern of peritonitis in childhood NS. Methods: This cross-sectional observational study was conducted in pediatric nephrology department of Bangabandhu Sheikh Mujib medical university (BSMMU). The 44 diagnosed patient of spontaneous bacterial peritonitis among childhood idiopathic NS were enrolled as cases. The peritoneal fluid was obtained following standard procedure and examined for gross appearance, cytogical and biochemical analysis, microscopic examination with gram stain and peritoneal fluid culture along with antibiotic sensitivity. Results: All patients had complaints of abdominal pain followed by fever, vomiting, lethargy and anorexia. All cases had edema and ascites followed by abdominal tenderness, abdominal wall rigidity, rebound tenderness and cellulitis in areas other than abdominal wall. Peritoneal fluid showed neutrophilic pleocytosis and exudative fluid. We observed 27.27% gram + cocci, 6.82% gram-bacilli in gram stain examination. Here, only 6.9% cases showed positive growth including 2.3% E. coli, 2.3% Pseudomonas, 2.3% Acinetobacter and remaining 93.1% cases showed no growth. We also described the antibiotic sensitivity pattern in this study. Conclusions: In our study, patients predominantly had abdominal pain, fever, edema, ascites and abdominal tenderness. We found only 6.9% cases showed positive growth which included E. coli, Pseudomonas and Acinetobacter and demonstrated the antibiotic sensitivity and resistance pattern for these organisms.